Study of general trends of modern development of ammonia production - Бабіченко, Анатолій Костянтинович; Азаров, Миколай Іванович; Бабіченко, Юлія Анатоліївна; Красніков, Ігор Леонідович; Лисаченко, Ігор Григорович (Technology audit and production reserves, 2014)
The evolution stages of synthetic ammonia production were considered in the paper. In the context of these stages, according to the results of analytical studies, general development trends of ammonia production in the present conditions, in particular for Ukraine, which cover both problems and individual tasks, required for overcoming and solving them were analyzed and determined. It was shown that the need to solve food program is associated with the trend of ever-increasing nitrogen fertilizers production volume, both in the world and in Ukraine, which is accompanied by a corresponding increase in the ammonia production volume. It was proved that, in the coming decades, the natural gas will continue to be the main raw material in the ammonia production technology. Herewith, a tendency to increase their energy efficiency by upgrading instrumental-technological design of the most energy intensive stages, in particular ammonia condensation, in order to reduce electricity and natural gas consumption rates, which can be achieved by utilizing low-grade heat of flows with the temperature less than 100° C is especially relevant for domestic units. The latter can be achieved by using steam-ejector refrigeration systems.